PENGARUH SUMUR RESAPAN DAN KOLAM RETENSI DI SISTEM DRAINASE UGM (Studi Kasus: Kampus Ugm Wilayah Timur) - , TRI NUGRAHA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Infrastructure development on University of Gadjah Mada raises issues regarding water resources which is the increasing of runoff discharge. UGM as an environmentally awareness campus should provide an example of a sustainable drainage system to reduce floods that occur in urban areas of Yogyakarta. This relates to the upstream of Kali Belik at the north of UGM that pass through the campus. UGM campus is inside of Kali Belik watershed thus affecting the runoff discharge flow to Kali Belik. If the dimension of the channel canât accommodate the flow of water passing through Kali Belik, overflow will happen and some areas of the city will be flooded. This research was conducted by collecting both primary and secondary data. Primary data were obtained from direct observations and surveys in the UGM campus environment. Secondary data were collected from the Directorate of Planning and Development UGM (DPP UGM) and the Directorate of Asset Maintenance and Management UGM (DPPA UGM). The data was analyzed and modeled using rational methods and flow routing to obtain runoff discharge, flood hydrograph for a retention pond with return period of 2, 5, 10 years and the condition of existing retention pond . Implementation of water conservation techniques in UGM is the existing infiltration wells in Region-1 (Faculty of Agriculture, Faculty of Forestry, Faculty of Agricultural Technology), 2 (Faculty of Social Political Science), 3 (Faculty of Psychology and UGM residence area), and 5 (Faculty of Animal Science) each has 7, 15, 12, and 3 wells . The number of wells in each catchment area can absorb water discharge for 0,02 m3/second